Strategi Guru SLB dalam Menyesuaikan Pembelajaran Berdiferensasi sesuai Kebutuhan Individu Siswa Berkebutuhan Khusus - Nurmayani Nurmayani; Qania Azmi; Fadillah Tasali; Inne Jeniarti; Dwi Ananda Putri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to identify and analyze the strategies implemented by Special School (SLB) teachers in adjusting learning content and modifying learning methods and media according to the individual needs of students with special needs. Differentiated learning is a crucial approach in inclusive education to accommodate the diversity of characteristics and learning needs of students. This study uses a qualitative approach with a descriptive method. The subjects of the study were teachers who teach at SLBN Autism North Sumatra. Data collection techniques were carried out through observation and interviews. The results of the study are expected to enrich the theory of differentiated learning in the context of inclusive education, as well as provide practical references for SLB teachers in designing and implementing more effective and responsive differentiated learning for students with special needs.